2010
DOI: 10.1111/j.1467-9450.2009.00736.x
|View full text |Cite
|
Sign up to set email alerts
|

Working memory resources in young children with mathematical difficulties

Abstract: Working memory (WM) (Baddeley, 1986, 1997) is argued to be one of the most important cognitive resources underlying mathematical competence (Geary, 2004). Research has established close links between WM deficits and mathematical difficulties. This study investigated the possible deficits in WM, language and fluid intelligence that seem to characterize 4- to 6-year-old children with poor early mathematical skills before formal mathematics education. Children with early mathematical difficulties showed poor perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 98 publications
2
37
1
6
Order By: Relevance
“…This indicates that better working memory performance on each component is associated with better mathematical performance, as suggested in several studies (e.g., Geary et al, 2004;Kroesbergen et al, 2009;Passolunghi et al, 2008). The working memory component that showed the strongest relation with mathematical skills was verbal updating, whereas inhibition and shifting showed the weakest relations, confirming findings reported in previously published studies (Kolkman et al, 2013).…”
Section: Unconditional Modelssupporting
confidence: 87%
See 1 more Smart Citation
“…This indicates that better working memory performance on each component is associated with better mathematical performance, as suggested in several studies (e.g., Geary et al, 2004;Kroesbergen et al, 2009;Passolunghi et al, 2008). The working memory component that showed the strongest relation with mathematical skills was verbal updating, whereas inhibition and shifting showed the weakest relations, confirming findings reported in previously published studies (Kolkman et al, 2013).…”
Section: Unconditional Modelssupporting
confidence: 87%
“…Inhibitory skills have also been found to reliably predict mathematics scores in typically developing young children (Bull and Scerif, 2001;Espy et al, 2004;St Clair-Thompson and Gathercole, 2006), and performance on inhibition tasks has been related to growth in mathematics scores across a time span of several months (Panaoura and Philippou, 2007). Moreover, inhibition has been found to already predict number sense, as an early form of mathematical proficiency (Kolkman, Hoijtink, Kroesbergen, & Leseman, 2013;Kroesbergen, Van Luit, Van Lieshout, Van Loosbroek, & Van de Rijt, 2009). However, differences between mathematics-disordered children and normal controls with regard to inhibition have not been found consistently (Censabella and Noël, 2008) and the involvement of inhibition in mathematical performance cannot be confirmed in every study (Andersson, 2008;Monette, Bigras, & Guay, 2011).…”
Section: Relations Between Working Memory and Mathematical Performancementioning
confidence: 96%
“…Andersson & Lyxell, 2007 & Passolunghi, 2009;Kyttälä et al, 2010;Passolunghi & Cornoldi, 2008;Passolunghi & Siegel, 2004). One possible account of this non-significant finding is that this study was performed on 11-13 year old children, whereas prior studies observing a non-numerical verbal working memory deficit in children with MLD have included 9-10 year old children.…”
Section: The Domain General Cognitive Deficit Hypothesiscontrasting
confidence: 48%
“…In spite of this, recent studies using a broad spectrum of working memory tasks (verbal and visual-spatial) demonstrate that children with MLD have deficits with both verbal and visual-spatial working memory functions (Andersson & Lyxell, 2007;Kyttälä, Aunio, & Hautamäki, 2010;Passolunghi & Cornoldi, 2008;Wilson & Swanson, 2001), whereas a few studies have found that MLD children only have a deficiency with visual-spatial working memory but not with verbal working memory (Andersson, 2010;Schuchardt, Maehler, & Hasselhorn, 2008).…”
Section: The Hypothesis Of a Domain General Cognitive Deficitmentioning
confidence: 92%
“…As stated by, for instance, Rittle-Johnson, and Siegler (1998), problems of validity can occur in studies suggesting that acquiring one type of knowledge has a causal influence on the future acquisition of another type of knowledge. Since such relationships could fully or partly be explained by a other variables, such as working memory (Kyttälä, Aunio, & Hautamäki, 2010) or motivation (Aunola et al, 2006;Gottfried, Marcoulides, Gottfried, Oliver, & Guerin, 2007), future studies should replicate the study of similar predictive relationships within a more comprehensive design. And even though Byrnes and Wasik (2009) convincingly reported that propensity factors (e.g.…”
Section: Discussionmentioning
confidence: 96%